Comparative analysis of organoid, air-liquid interface, and direct infection models for studying pathogen–host interactions in endometrial tissue - Zhang, Xin; Fan, Linyuan; Zhang, Li; Liu, Zhaohui (Scientific reports, 2025)
The endometrium is a critical component of female reproductive health. Endometritis can significantly affect women’s health, leading to complications such as infertility, pregnancy failure, and intrauterine adhesions. Therefore, establishing a reliable and effective model of endometritis is essential for advancing research in female reproductive health. The air-liquid interface culture models epithelial exposure to both air and medium, supporting the study of apical-basal polarity and immune responses, but lacks the three-dimensional structure of organoids. Microinjection delivers bacteria directly into the organoid lumen, facilitating the study of bacterial invasion and replication, though it requires advanced technical skills and may not fully replicate natural infections. The direct infection of organoids in suspension culture offers a more realistic model of ascending infections by exposing the basal epithelial surfaces to bacteria, more closely mimicking in vivo conditions. Among the models tested, the direct infection method most accurately mirrors the progression of E. coli infection, showing its advantage in studying bacterial adhesion, replication, and epithelial barrier disruption. Our comparative analysis of microinjection, direct infection, and the ALI model highlighted distinct advantages and challenges associated with each. Microinjection offers precise delivery but is hindered by technical complexity and equipment demands. The ALI model, despite its efficacy, requires extended culture times and limits direct visualization of cell development. Conversely, the direct infection model, which involves the simple removal of Matrigel, proves to be user-friendly, cost-effective, and permits continuous observation of cell behavior. Nonetheless, the direct infection model still presents certain limitations that warrant further optimization.